On the effectiveness of the use of online learning technologies in teaching English - Beisenbayeva, B.A.; Kopzhasarova, U.I. (KU Publ., 2021)
The article focuses on benefits of using online technologies at foreign language classes. Various opportunities and forms of distance learning in higher education institutions and also promising from authors’ point of view e-learning technologies, platforms, their strengths and drawbacks are analyzed in the work. Special attention is paid to the capabilities of the Zoom program as the most functional tool that allows teachers to conduct training sessions in the video conferencing mode. The authors suggest instructional techniques in the framework of distance learning, enabling to increase the efficiency of the transmission and perception of information that is necessary for students. The authors come to the conclusion that teachers’ task, at present, is to intensify the process of mastering the foreign language through the application of state-of-the-art technologies, facilitate each student’s activity in the process of distance learning and provide opportunities for their academic independence and creativity. The proper use of computer programs and Internet technologies in the framework of distance learning is of big importance in the improvement of the foreign language skills of students.
Ағылшын тілін онлайн оқыту кезінде интернет-ресурстарды пайдаланудың тиімділігі туралы
Об эффективности использования интернет-ресурсов в онлайн обучении английскому языку
Keywords: distance education; remote learning; multimedia and information technology; video conferences; traditional approaches; encourage; social networks; internet resources